Improving Occupational Performance in Pediatric Hematopoietic Cell Transplant Recipients. - Colman, Julia; Casto, Shelley Coleman; Wisner, Eliscia; Stanek, Joseph R.; Auletta, Jeffery J. (American Journal of Occupational Therapy)
Importance: There is a critical gap in the literature regarding the efficacy of occupational therapy interventions for pediatric hematopoietic cell transplantation (HCT) patients. Objective: To demonstrate that occupational therapy 4–5×/wk during inpatient hospitalization positively affects strength, coordination, and independence in activities of daily living (ADLs) of pediatric patients during HCT. Design: Retrospective study. Setting: Inpatient bone marrow transplant unit at a children's hospital. Participants: Thirty-two pediatric patients admitted for HCT. Outcomes and Measures: Patients were seen by an occupational therapist as part of an interdisciplinary program. Interventions included play and leisure engagement, upper extremity therapeutic exercises, fine motor activities, and ADL training. Strength, coordination, and daily living skills data were documented prospectively and analyzed retrospectively to compare differences between patients seen by occupational therapy at high versus low frequency. Results: For grip strength (dynamometer), fine motor dexterity (the 9-Hole Peg Test), and independence in ADLs (an ADL functional measure and the Pediatric Evaluation of Disability Inventory–Computer Adaptive Test Daily Activities), the high-frequency group had a significantly smaller decrease in performance from time of admission at pretransplant (baseline) to peak decline after transplant. Grip strength and ADL scores for the high-frequency group returned to baseline at time of discharge more readily than for the low-frequency group. Conclusions and Relevance: Participation in occupational therapy 4–5×/wk had positive effects on strength, coordination, and independence in ADLs for patients undergoing HCT. What This Article Adds: This article provides evidence that occupational therapists are an important part of the interdisciplinary team treating pediatric bone marrow transplant patients. It also demonstrates that occupational therapy interventions delivered at a high frequency can have a positive impact on upper extremity strength and independence in ADLs.